Perancangan Sistem Pelayanan Antrian Badan Penyelenggara Jaminan Sosial Kesehatan - Frecilia (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2021)
BPJS Kesehatan is a public legal entity that is responsible to the President and functions to organize a health insurance program for all Indonesians Patient users of BPJS Kesehatan must come queue since dawn till noon just to meet the doctor. In addition, there are also several prospective patients and non patients who try to seek personal gain by selling queue numbers to other prospective patients. The BPJS Health queue service system is designed using the First Come First Serve queuing method which aims to set the queue of patients in accordance with the time taken. The results of this study are a queuing service system that can make referrals and produce schedules and queue numbers for the patients.